Work in the platform economy: Deliveroo riders in Belgium and the SMart arrangement - Jan Drahokoupil; Agnieszka Piasna (European Trade Union Institute (ETUI), 2019)
This paper presents a case study of the food delivery platform, Deliveroo, in Belgium in 2016-2018. The case offers insights on the nature of platform work, the workers who perform it, the preferences of workers, the strategy of the platforms, and the role of local regulations. Interestingly, Deliveroo in Belgium employed workers through an intermediary, SMart, and we also observed the termination of their co-operation in the period under analysis. Using administrative data provided by SMart and a survey of workers, we analyse patterns of work and also focus on pay. We investigate the characteristics of the workers, their preferences regarding working conditions and their motivation for engaging in platform work. We identify that the jobs are lowhours and low-income, performed primarily by precarious student workers. We show that the SMart arrangement was motivated primarily by the specifics of the Belgian tax system. Even so, it provided workers with protections that they valued, including income security. Contrary to what the platform claimed, the abandonment of the SMart system did not offer the riders the flexibility they desired. Instead, it reduced their degree of autonomy and control in relation to the platform.
Keywords: 330; digital services; hospitality industry; Working conditions; Belgium; Digitale Dienste; Gastronomie; Arbeitsbedingungen; Belgien